Accurate detection of Zika virus IgG using a novel immune complex binding ELISA. Issue 1 (11th November 2020) - Ehmen, C.; Medialdea‐Carrera, R.; Brown, D.; de Filippis, A.M. Bispo; de Sequeira, P.Carvalho; Nogueira, R.M. Ribeiro; Brasil, P.; Calvet, G.A.; Blessmann, J.; Mallmann, A.‐M.; Sievertsen, J.; Rackow, A.; et al.
Abstract: Objectives: Accurate serological assays are urgently needed to support public health responses to Zika virus (ZIKV) infection with its potential to cause foetal damage during pregnancy. Current flavivirus serology for ZIKV infections lacks specificity due to cross‐reacting antibodies from closely related other flaviviruses. In this study, we evaluated novel serological tests for accurate ZIKV IgG detection. Methods: Our ELISAs are based on immune complex binding. The high specificity is achieved by the simultaneous incubation of labelled ZIKV antigen and unlabelled flavivirus homolog protein competitors. Two assays were validated with a panel of 406 human samples from PCR‐confirmed ZIKV patients collected in Brazil ( n = 154), healthy blood donors and other infections from Brazil, Europe, Canada and Colombia ( n = 252). Results: The highest specificity (100% [252/252, 95% confidence interval (CI) 98.5–100.0]) was shown by the ZIKV ED3 ICB ELISA using the ED3 antigen of the ZIKV envelope. A similar test using the NS1 antigen (ZIKV NS1 ICB ELISA) was slightly less specific (92.1% [232/252, 95% CI 88.0–95.1]). The commercial Euroimmun ZIKV ELISA had a specificity of only 82.1% (207/252, 95% CI 76.8–86.7). Sensitivity was high (93–100%) from day 12 after onset of symptoms in all three tests. Seroprevalence of ZIKV IgG was analysed in 87 samples from Laos (Asia) confirming that the ED3 ELISA showed specific reactions in other populations. Conclusions: The novel ED3 ICB ELISA will be useful for ZIKV‐specific IgG detection for seroepidemiological studies and serological diagnosis for case management in travellers and in countries where other flavivirus infections are co‐circulating.